2015
DOI: 10.1371/journal.pone.0144770
|View full text |Cite
|
Sign up to set email alerts
|

DCE-MRI for Pre-Treatment Prediction and Post-Treatment Assessment of Treatment Response in Sites of Squamous Cell Carcinoma in the Head and Neck

Abstract: Background and PurposeIt is important to identify patients with head and neck squamous cell carcinoma (SCC) who fail to respond to chemoradiotherapy so that they can undergo post-treatment salvage surgery while the disease is still operable. This study aimed to determine the diagnostic performance of dynamic contrast enhanced (DCE)-MRI using a pharmacokinetic model for pre-treatment predictive imaging, as well as post-treatment diagnosis, of residual SCC at primary and nodal sites in the head and neck.Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…In distinction, King et al [84] observed that the posttherapy residual masses with persistent tumors had higher permeability or perfusion measures, including higher k ep and area under the contrast curve, than those with complete response. These studies show the feasibility of using DCE-MRI for surveillance imaging.…”
Section: Detection Of Recurrencementioning
confidence: 99%
“…In distinction, King et al [84] observed that the posttherapy residual masses with persistent tumors had higher permeability or perfusion measures, including higher k ep and area under the contrast curve, than those with complete response. These studies show the feasibility of using DCE-MRI for surveillance imaging.…”
Section: Detection Of Recurrencementioning
confidence: 99%
“…However, perfusion measured by MRI has been used to assess the therapeutic effects and long-term prognosis for patients with malignancies. The perfusion level of tissues was suggested to potentially predict the tumor sensitivity of CRT [26,27]. Lai et al [12,13] reported that f could effectively distinguish residual tumors of NPC from radiation-related fibrous tissues, as well as tumor stages.…”
Section: Discussionmentioning
confidence: 99%
“…First, due to precontrast inflow phenomenon and postcontrast induced signal loss from high concentration of contrast agent at peak arterial enhancement, it was difficult to obtain an accurate AIF with perfusion MR imaging, which might make an adverse influence on the measurement of perfusion parameters. 32,33 Second, we did not investigate the reproducibility of perfusion parameters across different MR devices, field strengths or centers, therefore, further study is necessary before this imaging technique is extensively applied in clinical practice. Finally, there is no linear relationship between concentration of contrast agent and signal intensity, this nonlinearity is most pronounced at higher contrast concentration, which might undermine the value of perfusion parameters in reflecting tumor vasculature.…”
Section: Discussionmentioning
confidence: 99%